Cost consequence analysis of use of a balloon expandable vascular access system and standard vascular sheath for transcatheter aortic valve implantation. (2nd November 2018) - Asgar, Anita W.; Pighi, Michele; Millan, Xavi; Khan, Razi; Dorval, Jean-Francois; Ibrahim, Reda; Azzalini, Lorenzo; Bonan, Raoul
Abstract: Background: Vascular complications are an important complication of transcatheter aortic valve implantation and are associated with increased morbidity and mortality as well as cost. The Solopath device is an expandable vascular access system that has previously been shown to be associated with lower rates of vascular complications. This study sought to evaluate the impact of the use of this system on vascular complications and costs in a decision model analysis. Methods: A cost-consequence analysis was undertaken utilizing event rate data from the PARTNER trials and a published retrospective analysis of the Solopath device. The decision model estimated costs and benefits in a hypothetical cohort of patients with aortic stenosis undergoing TAVI using either a standard sheath or Solopath. The modeled analysis compared the occurrence of vascular complications and mortality at 30 days and 1 year using TreeAge Pro. Results: The decision model demonstrated that use of the Solopath sheath resulted in 36 fewer major vascular complications, three fewer deaths at 30 days, and five fewer deaths at 1 year, resulting in a discounted cost savings of 846 CDN. Results were sensitive to decreasing rates of vascular complications with newer generation devices, however maintained modest cost-savings. Conclusions: Reduction in vascular complications is an important part of improving care for TAVI patients. The Solopath vascular access device offers an alternative to standard sheaths with a potential reduction in complications and cost-savings.